Prevalence and Antimicrobial Sensitivity Pattern of Gram Negative Rods in Blood Cultures: A Tertiary Care Hospital Study - Almas Raza, Sadaf Munir, Nasir Rashid, Rameesha Muzafar, Sheema Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Prevalence and antimicrobial susceptibility pattern of gram negative rods in blood cultures. Methods: Cross-sectional study performed in Pathology section, Pak Red Crescent Teaching hospital, Lahore for one year i.e. 01-11-2019 to 31-12-2020. After approval from ethical committee, 1100 blood samples were taken for C/S from various sections of the Hospital. The antimicrobial sensitivity was done by Kirby-Bauer disc diffusion method as approved by Clinical and Laboratory Standard Institute (CLSI). Results: Out of 1100 Blood samples, 65 samples of blood cultures were positive for Gram –ve Rods. The prevalence of Gram negative Rods in blood specimens was only 6%. Out of 6% gram –ve rods, 12% were E.coli, 9% Klebsiella, 3% Enterobacter cloacae, 45% Salmonella, 2% Proteus, 17% Pseudomonas, 10% Acinetobacter and 2% were serretia. Conclusion: The prevalence of Gram negative rods in blood specimens was only 6%.